One of our own eaudiobook An audio original thriller. - Berry, Lucinda (Simon & Schuster Audio Originals, 2024)
A suicide prevention hotline volunteer answers a call that turns her world upside down in this edge-of-your-seat audio original thriller by the bestselling author of The Perfect Child and The Best of Friends , performed by A.J. Cook ( Criminal Minds ) and Tessa Albertson ( Younger ). Felicia, a single mother and lawyer by day, volunteers at a local crisis center to give back to her tightknit community in a small Wisconsin town. One night, she answers a horrifying call: through tears, a frantic teenage girl tells her that she was a victim of sexual assault at a local house party. Felicia is shocked, and breaking protocol, she begins communicating with the girl on her own, determined to keep her safe and hold her assailants accountable. But as she gets closer and closer to the truth, she can't shake the feeling that she and the girl are connected by more than the phone call. As the girl shares more details, Felicia begins to think the unthinkable—someone close to her may be involved in this heinous crime. As Felicia earns the girl's trust and more facts emerge about the incident, she faces a gut-wrenching battle between her protective instincts and the moral responsibility to do what's right. This taut thriller is the perfect listen for fans of The Push , Wrong Place Wrong Time , and We Need to Talk About Kevin .